Green Algae as a Drug Delivery System for the Controlled Release of Antibiotics. Issue 70 (18th November 2020) - Shchelik, Inga S.; Sieber, Simon; Gademann, Karl
Abstract: New strategies to efficiently treat bacterial infections are crucial to circumvent the increase of resistant strains and to mitigate side effects during treatment. Skin and soft tissue infections represent one of the areas suffering the most from these resistant strains. We developed a new drug delivery system composed of the green algae, Chlamydomonas reinhardtii, which is generally recognized as safe, to target specifically skin diseases. A two‐step functionalization strategy was used to chemically modify the algae with the antibiotic vancomycin. Chlamydomonas reinhardtii was found to mask vancomycin and the insertion of a photocleavable linker was used for the release of the antibiotic. This living drug carrier was evaluated in presence of Bacillus subtilis and, only upon UVA1‐mediated release, growth inhibition of bacteria was observed. These results represent one of the first examples of a living organism used as a drug delivery system for the release of an antibiotic by UVA1‐irradiation. Abstract : Algae control the release : A new approach for antibiotic caging and controlled release was developed using Chlamydomonas reinhardtii . The algae were covalently modified with vancomycin, and using a photocleavable linker, light‐mediated release of an antibacterial agent from the cell surface and inhibited the growth of Bacillus subtilis (see figure).